Button battery versus stacked coin ingestion: A conundrum for radiographic diagnosis. (November 2019) - Whelan, Rachel; Shaffer, Amber; Dohar, Joseph E.
Abstract: Objectives: Given the potential for devastating complications associated with esophageal impaction of a button battery, there is a need to distinguish between a button battery and look-alike stacked coins at the time of presentation. Given there have been no studies analyzing differences in radiographic density between these two entities, the study objective was to determine if a difference exists between esophageal coin and button battery radiographic density on plain radiograph and to describe the operative and treatment course following these two distinct entities of ingestion. Methods: Retrospective case series following button battery or stacked coin ingestion in a tertiary care pediatric hospital from 2003 to present. Radiographic density of each button battery and stacked coin was calculated by dividing the foreign body radiographic density by the mean density of two background radiographic sections. Radiographic density of coins versus batteries was compared using t-tests. Results: There were 22 patients identified with button battery ingestion and 47 with stacked coins. Median (range) radiographic density of button batteries on anteroposterior view was 1.16 (0.37–2.19) x background compared to 1.13 (0.09–2.65) x background of stacked coins, p = 0.198. There was similarly no statistically significant difference in lateral views, p = 0.622. Conclusion: Our study suggests that radiographic density measured on diagnostic x-ray does not prove a reliable adjunctive measure to distinguish an innocuous stacked coin ingestion from the far more ominous button battery and highlights the need for prompt operative evaluation for any suspected button battery ingestion.